2022
DOI: 10.1177/15353702221134097
|View full text |Cite
|
Sign up to set email alerts
|

Absence of antibody responses to SARS-CoV-2 N protein in COVID-19 vaccine breakthrough cases

Abstract: Understanding the risk factors for breakthrough coronavirus disease 2019 (COVID-19) (BC19) is critical to inform policy. Herein, we assessed Delta (Lineage B.1.617.2) variant-specific effectiveness of the BNT162b2 (Pfizer) vaccine and characterized Delta-driven BC19 cases (fully vaccinated individuals who get infected) with known-time-since-vaccination. In this longitudinal prospective study (January 21–October 30, 2021), 90 naïve and 15 convalescent individuals were enrolled at the initiation of vaccination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…This finding could indicate that individuals with higher anti-S1 IgG concentrations at the time of infection produce fewer copies of the SARS-CoV-2 virus during infection inducing lower levels of anti-NCP antibodies (Figure 1C). This result is in line with the findings of a study where authors observed a reduced/delayed increase or complete absence of NCP antibodies after breakthrough infection (Vu et al, 2022).…”
supporting
confidence: 92%
“…This finding could indicate that individuals with higher anti-S1 IgG concentrations at the time of infection produce fewer copies of the SARS-CoV-2 virus during infection inducing lower levels of anti-NCP antibodies (Figure 1C). This result is in line with the findings of a study where authors observed a reduced/delayed increase or complete absence of NCP antibodies after breakthrough infection (Vu et al, 2022).…”
supporting
confidence: 92%